Knowledge, attitude and practice towards facemask use amid the COVID-19 pandemic among public transport drivers in Debre-Tabor town, Ethiopia - Wubet, Gashaw Mehiret; Zimamu, Libsuye Yalgaw (Journal of Community Medicine and Health Solutions, 2022)
Background: For the prevention of respiratory infection similar to the current pandemic COVID-19, face masks are considered an effective method. Coronavirus disease (COVID-19) is a highly transmittable virus that continues to disrupt livelihoods, particularly those of low-income segments of society, around the world has poor knowledge towards facemask at the same time has huge gape towards attitude which affects the behaviors. Therefore this study was aimed to assess knowledge, attitude, and practice towards facemask use amid the COVID-19 pandemic among public transport drivers in Debre-Tabor town, Ethiopia, 2021. Methods: A cross-sectional study was conducted among 407 public transport drivers in Debre-Tabor town from July to August 2021. The study participants were selected using a simple random sampling technique after proportionally allocating the sample size from the total number of public transport drivers, and finally, study subjects were elected continuously working in Debre- Tabor Town public transport drivers. The data were collected by trained data collectors using a structured questionnaire with face-to-face interview administered questioners and an on-the-spot observational checklist. The collected data were checked, coded, and entered into SPSS version 23, and for data cleaning and analysis. Result: A total of 407 drivers responded to the questionnaire with a response rate of 96.4% were participated in this study. The mean age was 32.75 years (range: 19-45 years). Among them majority was male 383(94.1%) and the majority of 177(43.5%) were Bajaj drives. Among the responders, 114(28%) used radio to gather information, and 41(10.1%) drivers where were caught by COVID-19, but, only 30(7.4%) were vaccinated COVID-19 vaccine. Knowledge, attitude and practices regarding facemask use among these drivers were 368(90.4% [95% CI: 87.7-93.1]). 163(40% [95% CI: 37.5% - 43.2%]), and 23 ((5.6%) [95% CI: 3.7% - 8.3%]) Regarding facemask use against COVID-19 infection respectively. Conclusion and recommendation: The current study was able to demonstrate 90.4% of drivers had good knowledge. Positive attitude and practice levels of face mask use among drivers were less than half of them or 40%, and 5.6% respectively. There is a high supply of Surgical Face masks but poor attitude and practice. Almost all of the participants don’t wear a face mask despite having good knowledge about the transmission routes of COVID-19. The government COVID-19 prevention task force or health sector should be continued their awareness creation to bring behavioral change for the implementation of the COVID-19 prevention method, especially facemask.